Securing E-governance: a blockchain-based framework for tamper-proof PDF document exchange - Mishra, Priyanka; Ganesan, R. (Frontiers in Blockchain, 2025)
E-governance depends on the secure exchange of digital documents, with PDFs widely used for official communication. However, threats such as shadow attacks and policy tampering undermine integrity and trust. This paper proposes a blockchain-based framework that secures PDF workflows by recording complete document hashes and metadata on an immutable ledger. By integrating Policy-based Governance infrastructure, the system strengthens digital signature verification and resists tampering, even under Man-in-the-Middle (MITM) conditions. Evaluation on 1,000 official PDFs shows that the proposed framework achieves 93.1% detection of shadow attacks with 98.4% precision and only 1.6% false positives, compared to traditional PKI methods that failed to detect any tampering. The approach maintains efficiency, scalability, and cost-effectiveness, providing a resilient foundation for secure, transparent, and trustworthy e-governance services.